Sistem Pendukung Keputusan Menentukan Titik Lokasi Pembangunan Jalan Rabat Beton Pada Desa Aek Sundur Dengan Metode Complex Proportional Assessment (COPRAS) - Simbolon, Ali Husein (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2024)
Decision Support Systems (DSS) have become an important element in planning and decision making. Decision support systems have also been widely applied in various aspects of life to assist in the decision making process. One of them is determining the location of the concrete rebate road construction location. The problem in determining the location for concrete rebate construction in Aek Sundur Village is that there are several obstacles such as the level of road damage, road requirements, road volume, and road maintenance period, so that not all roads can be built.The right solution to this problem is to ensure that the constraints and security of the data used in determining the location point for the construction of the concrete rebate road must be correct, thereby reducing the risk of errors in determining the construction point.The results of this research will provide recommendations regarding the optimal location for the construction of a concrete rebate road based on a proportional assessment of previously determined criteria. So the Belimbing village road, cemetery road and Sihambeng road are roads that are suitable to be built based on the criteria used.